Evidences of Long‐Chain Branching in Ziegler‐Natta Polyethylene Homopolymers as Studied via SEC‐MALS and Rheology. Issue 1 (23rd August 2013) - Yu, Youlu; Rohlfing, David C.; Soares, João B.P.
Summary Comprehensive polymer architectural studies were carried out on a group of Ziegler‐Natta (Z‐N) polyethylene homopolymers via size‐exclusion chromatography coupled with multi‐angle light scattering (SEC‐MALS) and rheology. Although Z‐N resins are traditionally viewed as linear polymers, both SEC‐MALS and rheology results strongly indicate that there are topological variations, presumably long‐chain branching (LCB) or possibly hyper‐branches, in this group of supposedly linear Z‐N homopolymers. These Z‐N homopolymers exhibit very complex elution behavior that resulted in anomalous elution profiles in SEC. It appeared that some high molecular weight (MW) and long‐chain branched components followed a non‐size exclusion separation mechanism on SEC columns, co‐eluting with low MW and linear polyethylene components, causing a delayed elution. The possible origin of LCB in these Z‐N polymers is also discussed.